Is the FTAA at an impasse? The key players US and Brazil - Susanne Gratius (Stiftung Wissenschaft und Politik (SWP), 2003)
If everything goes as planned, 34 states in the Western Hemisphere will sign a free trade agreement in less than a year and half. With a 13 trillion dollar economy (40% of the world's GNP) and 820 million potential consumers, the Free Trade Area of the Americas (FTAA) would be the world's largest trading block and an FTA of continental dimensions. Although negotiations are continuing - with the US and Brazil serving as co-chairs since November 2002 -, thirteen years after the initial launch of the project, doubt, in the US and Latin America, is growing that a free trade zone stretching from Tierra del Fuego to Alaska will ever exist.(SWP Comments / SWP)
Keywords: 320